Burden of anxiety in Adolescent: A community-based study in Western Uttar Pradesh - Gupta, Sudhir Kumar; Prabhakar, Anish; Kumar, Amit; Arif, Nawaid; Yadav, Sachin Singh; Ganta, Shilpa Reddy (Indian Journal of Community Health, 2023)
Background: Anxiety is a prevalent issue among adolescents and can adversely affect their academic performance and everyday functioning. Aims & Objectives: To estimate the prevalence of anxiety among adolescents in urban and rural areas and to study the socio-demographic correlates of anxiety among adolescents in urban and rural areas. Methods: A comprehensive survey was conducted in the field practice area of Department of Community Medicine of a Medical College in western district of Uttar Pradesh. The survey was aimed at young people between the ages of 10 and 19 who lived in the practice area of the medical college. Result: The burden of anxiety was observed to be 19.6 % (n=92). Female gender, urban residence, early adolescent age-group (10-13 yr), nuclear family, day-time somnolence and family history of mental illness were factors having statistical significance. Poor education level of parents was also statistically significant. Physical activity and substance abuse did not have significant contribution in burden of anxiety. Conclusion: Anxiety in adolescents is a significant issue influenced by various factors. Early intervention and support are crucial.